Evaluation of quality of life related to melasma (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To synthesize the scientific production about quality of life related to melasma and to analyze the instruments used to evaluate the construct. Method: Integrative revision with search in Web of Science databases, Lilacs, PubMed, Scopus, Google Scholar and Embase. All articles published in the literature up to 2013 were included. Results: The sample consisted of 26 articles. Most of the research was realized in the United States of America (30.7%), followed by Brazil (38.4%) and South Korea (38.4%). The intervention studies were emphasized (57.5%),using Melasma Quality of Life Scale (MELASQol) as a specific instrument. Conclusion: This review allowed to identify that the assessment of quality of life related to melasma has been widely discussed in the literature. As for the instruments used to evaluate the construct, there is only one specific, translated and validated in several countries, but whose development did not follow the classic stages of psychometry.
Keywords: Melanosis; Quality of life; Nursing